Pemikiran Geopolitik Islamic State of Irak and Syria (ISIS) - Wibowo, Prihandono; Hapsari, Renitha Dwi; Ascha, Muchammad Chasif (Indonesia Center for Middle East Studies, 2023)
Geopolitical studies developed significantly. While classical geopolitical studies focus on interactions between countries in controlling areas considered strategic, contemporary geopolitical studies open up studies on how non-state actors also embrace geopolitical thinking. Contemporary geopolitical studies include the use of geopolitical elements by terrorist groups. Regarding actual developments, ISIS is different from other terrorist groups. ISIS proclaimed itself as a caliphate, controled a large territory, and acted like a state. In the 2013-2017 era, before finally being defeated by the Iraqi and Syrian militaries and their coalitions, ISIS controlled strategic areas, including several cities in Iraq and Suriah. This study aims to understand the construction of geopolitical thinking developed by ISIS. The method uses in this study is a qualitative method by analyzing various documents published by ISIS